HBOT an effective adjuvant therapy in the treatment of Bell’s palsy: A case series - Divya Singh; Harshbir Singh Chaudhry; Chandra Sekhar Mohanty; Kuldeep Kumar Ashta (Journal of Family Medicine and Primary Care)
Bell’s Palsy is characterized by sudden onset facial paralysis due to dysfunction of the facial nerve. While conventional treatments exist, the potential of Hyperbaric oxygen therapy (HBOT) in managing this condition remains underexplored. This study aims to evaluate the efficacy of HBOT as an additional intervention in Bell’s Palsy cases. Seven individuals with Bell’s Palsy were selected for this study and treated with a combination of standard therapy along with sessions of HBOT. The treatment regimen, frequency of HBOT sessions, and follow-up protocols were standardized across all cases. Following the combined therapy approach, significant improvements were observed in all seven cases. Reduction in facial paralysis, improved muscle strength, and enhanced facial mobility were notable outcomes. Furthermore, compared to historical data on Bell’s Palsy recovery rates with standard treatment alone, the addition of HBOT seemed to expedite the recovery process. This case series demonstrates promising results regarding the efficacy of HBOT as an adjunct therapy for Bell’s Palsy. The findings suggest that incorporating HBOT into the treatment protocol for Bell’s Palsy could potentially enhance facial nerve recovery and overall outcomes. Further research with larger sample sizes and controlled studies is warranted to solidify these preliminary findings and establish HBOT’s role in the management of Bell’s Palsy.